2013
DOI: 10.1186/2193-1801-2-678
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum BDNF levels associated with moderate-intensity exercise in healthy young Japanese men

Abstract: PurposeThe purpose of this study was to examine the influence of acute moderate-intensity exercise on serum brain-derived neurotrophic factor (BDNF) levels in healthy young Japanese men. BDNF is one of a family of neurotrophic factors involved in neuronal transmission, modulation and plasticity. Previous human-based studies have demonstrated that acute exercise leads to increases in BDNF; however, to date there has been no study conducted among Japanese male subjects.MethodsForty young adult Japanese men (aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
(43 reference statements)
4
9
0
1
Order By: Relevance
“…Also, the increase in its levels after the chronic training may be caused by the increase in gene expression and activating the transcription pathways. Therefore, increase in the Brain-derived neurotrophic factor levels, aside from its roles in neurogenesis and brain health, plays a critical role in central and periph- Inconsistent with our findings, some studies reported a decrease or no changes in the levels of brain-derived neurotrophic factor after physical activity (24)(25)(26)(27). This can be due to the effect of type and intensity of exercise, age and physical fitness levels and health status of individuals on the synthesis, as well as release of brain-derived neurotrophic factor into blood stream.…”
Section: Discussionsupporting
confidence: 78%
“…Also, the increase in its levels after the chronic training may be caused by the increase in gene expression and activating the transcription pathways. Therefore, increase in the Brain-derived neurotrophic factor levels, aside from its roles in neurogenesis and brain health, plays a critical role in central and periph- Inconsistent with our findings, some studies reported a decrease or no changes in the levels of brain-derived neurotrophic factor after physical activity (24)(25)(26)(27). This can be due to the effect of type and intensity of exercise, age and physical fitness levels and health status of individuals on the synthesis, as well as release of brain-derived neurotrophic factor into blood stream.…”
Section: Discussionsupporting
confidence: 78%
“…In the studies of Schmolesky et al and Cho et al that involves measuring and validating the basal serum of BDNF values stated that the levels of basal BDNF values were ranged from 22.94 ± 9.12 ng / mL -24.95 ± 7.28 ng / ml in healthy male and female populations [15]. Low serum BDNF levels are found in people with a tendency toward behavioral mental disorders, such as anxiety, panic attacks, depression, memory disorders, and schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Under the present test conditions, BDNF values of tetraplegic athletes at rest were slightly higher or rather at the upper limit in comparison with previously reported values in able-bodied subjects. 2,3,27 Knaepen et al 2 summarized a high variability in basal values of 1.5-30.9 ng ml − 1 in able-bodied subjects. The data by Rojas Vega et al 20 in paraplegic athletes were somewhat higher than those in our study (Table 1).…”
Section: Discussionmentioning
confidence: 99%